PEMAHAMAN SISWA SMP DALAM EFISIENSI ALGORITMA SARINGAN ERASTOTHENES: indonesia - Maharani, Devina Shafira; Harisman, Yulyanti (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
The logic of shape, number, and sequence is the subject of mathematics. We use mathematics in everything we do. Available everywhere. Everything we use every day—computers, software, hardware, art, money, engineering, sports, and even ancient and modern architecture is built around it. In the realm of number theory, mathematicians study various aspects of prime numbers, including the distribution of prime numbers, ordering patterns of prime numbers, and methods for generating prime numbers. Even the most ancient and rudimentary societies used mathematics, and since the beginning of history, mathematical discoveries have been made. at the forefront of every civilized civilization. This is simple but can be applied to many phenomena in everyday life, making an Ancient Greek mathematician from the Hellenestic era named Erastothenes successful in being the person who created an extraordinary discovery, namely, the Erastothenes Sieve. Therefore, the aim of this research is to provide encouragement to junior high school students to understand and be interested in studying mathematics, especially the Erastothenes measurement method and then apply it in everyday life. This type of research is qualitative research with a descriptive approach and literature review method. The instruments used in this research are tests, interviews and documentation. The results of this research show the level of students' understanding of the Sieve of Eratosthenes.